2020
DOI: 10.1097/mog.0000000000000605
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome: update and clinical advice for prevention, diagnosis and treatment

Abstract: Purpose of review The aim of this review is to provide a brief overview of the refeeding syndrome, to discuss more recent advice on diagnosis and treatment, and to raise awareness of this still poorly understood metabolic condition. Recent findings To date, evidence regarding the refeeding syndrome has been very limited. A number of reviews and case reports exist, but only a few are randomized trials. Recently, it has been shown that the vast majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 13 publications
1
25
0
5
Order By: Relevance
“…In the presence of severe underweight or weight loss, prolonged fasting period, and/or low electrolyte concentrations, the risk of RFS is particularly high [30]. In 2006, the National Institute for Health and Clinical Excellence (NICE) guidelines [48] reported the risk factors to identify people at low or high risk for RSF.…”
Section: Population At Risk For Rfsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of severe underweight or weight loss, prolonged fasting period, and/or low electrolyte concentrations, the risk of RFS is particularly high [30]. In 2006, the National Institute for Health and Clinical Excellence (NICE) guidelines [48] reported the risk factors to identify people at low or high risk for RSF.…”
Section: Population At Risk For Rfsmentioning
confidence: 99%
“…Owing to the risk of fluid overload, sodium and hydration should be provided cautiously, until the patient is metabolically stable [38]. In [30].…”
Section: Prevention and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by an imbalance of electrolytes, mainly phosphate, potassium, magnesium, and calcium, and by vitamin disturbances, which can lead to impaired organ functioning (2,3). Data from the literature suggest a tendency to high mortality in this population, especially among malnourished, older, HIV, and critically ill patients (2,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…RFS incidence largely ranges from 0 % to 80 % according to the definition used and the population studied (2). Clinical, biochemical, and nutritional criteria allow early identification of the risk for RFS, and considering that electrolyte shifts occur in the first 3 days after NT initiation, it is recommended to monitor electrolytes during this period (1,3,4,6). This metabolic condition should be screened and monitored closely, although some studies have suggested that health professionals may be unaware of RFS (3,7).…”
Section: Introductionmentioning
confidence: 99%